Prevalence of skin infections caused by Panton-Valentine leukocidin-positive methicillin-resistant Staphylococcus aureus in Japan, particularly in Ishigaki, Okinawa. Issue 11 (November 2017) - Takadama, Shunsuke; Nakaminami, Hidemasa; Aoki, Sae; Akashi, Megumi; Wajima, Takeaki; Ikeda, Masami; Mochida, Atsushi; Shimoe, Fumiko; Kimura, Kumiko; Matsuzaki, Yasushi; Sawamura, Daisuke; Inaba, Yoichi; et al.
Abstract: The prevalence of Panton-Valentine leukocidin gene ( pvl )-positive community-acquired methicillin-resistant Staphylococcus aureus USA300 clone, which is designated as the ST8-staphylococcal cassette chromosome (SCC) mec type IV (ST8-IV) lineage, is a major public health concern worldwide. Thus, to elucidate the prevalence and characteristics of pvl -positive community-onset MRSA in Japan, we conducted a molecular epidemiological analysis for 854 S. aureus isolates obtained from outpatients with skin infections during 2013 and 2014. The isolation rate of MRSA was 25.6% (219 isolates), and the ratio of pvl -positive MRSA was 13.2% (29 isolates). Notably, the proportion (93.8%) of pvl -positive isolates was particularly high among MRSA isolates from Ishigaki island in Okinawa. Pulsed-field gel electrophoresis and multilocus sequence typing showed that the pulsotype C isolates (11 isolates) were typical USA300 clones with arginine catabolic mobile element (ACME) type I-CC8-IV lineages and prevalent on the main island of Japan (Honshu). Pulsotypes A (11 isolates) and B (four isolates) consisted of ACME-negative CC8-IV clones and were specific for Ishigaki island. Both USA300 and Okinawa-Ishigaki specific clones were associated with deep-seated skin infections, such as furuncle and cellulitis. Pulsotypes D (two isolates) and E (one isolate) were ACME-negative clonal complex (CC) 59-IV clones and were related to superficial skin infections, such as impetigo. Our findings revealed that pvl -positive MRSA associated with deep-seated skin infections are spreading in Japanese communities, particularly in Ishigaki, Okinawa.